Laparoscopic abdominoperineal resection for the treatment of a mucinous adenocarcinoma associated with an anal fistula. - Chrysikos, Dimosthenis; Mariolis-Sapsakos, Theodoros; Triantafyllou, Tania; Karampelias, Vasileios; Mitrousias, Apostolos; Theodoropoulos, George (J Surg Case Rep, 2018)
Mucinous adenocarcinoma associated with an anal fistula is a rare oncologic entity which may pose diagnostic and therapeutic challenges for Surgeons and Medical Oncologists. Few reported cases without definite therapeutic guidelines exist. It represents 2-3% of all gastrointestinal malignancies and arises from chronic anal fistulas, ischiorectal or perianal abscesses. We report a case of perianal mucinous adenocarcinoma in a 65-year-old male initially surgically treated multiple times for a recurrent fistula in ano of 5 years duration. He presented with an ischiorectal and a perianal fistula. Incisional biopsy from fistulotomy revealed mucinous adenocarcinoma. Contrast enhanced computed tomography scan and magnetic resonance imaging showed a localized perianal growth of a tumor which was further evaluated with colonoscopy. With no evidence of metastasis, we performed a laparoscopic abdominoperineal resection (APR). Two years follow-up after APR and without adjuvant chemotherapy there is not any evidence of recurrence or distant metastasis.